Linking data on women in public family law court proceedings concerning their children to mental health service records in South London - Rachel Pearson; Amelia Jewell; Linda Wijlaars; Stuart Bedston; Emily Finch; Karen Broadhurst; Johnny Downs; Ruth Gilbert (International Journal of Population Data Science, 2021)
Introduction Maternal mental health problems and substance misuse are key risk factors for child neglect or abuse and court-mandated placement into care. Linkage between mental health records and family court data could raise awareness about parent mental health needs and inform approaches to address them.